Analisis Kebutuhan Pengembangan Media Pembelajaran Interaktif Berbantuan Genially Pada Materi Sistem Koloid Terintegrasi Etnosains untuk Menumbuhkan Kemampuan Berpikir Kritis - Viga Aprilia Putri; Yusnaidar Yusnaidar; Firdiawan Ekaputra; Wilda Syahri; Epinur Epinur; Desy Marlina (Entalpi Pendidikan Kimia, 2026)
The colloidal system is a high school chemistry topic that examines the characteristics of fine particles within a dispersing medium. This material is often considered difficult by students due to its abstract nature, requiring a deep understanding of the types and properties of colloids and their daily applications. This condition indicates a need for innovation in learning media capable of connecting scientific concepts with contexts that are easier for students to understand. Through an ethnoscience approach that integrates local knowledge, students are encouraged to understand the material contextually and in relevance to local culture. This study aims to analyze the need for developing Genially-assisted interactive learning media on colloidal systems integrated with ethnoscience, focusing on fostering critical thinking skills. The research method used is descriptive qualitative, with data collection techniques consisting of questionnaires and interviews with students and chemistry teachers at SMA Negeri 17 Muaro Jambi. Data were analyzed descriptively. The results of the needs analysis show that 60.7% of students experience difficulty understanding colloidal material and 89.3% of students require media with a combination of text, images, video, and animation. Furthermore, both students and teachers strongly agree with the development of Genially-assisted interactive learning media that can be used at school or at home to support learning processes that foster critical thinking skills.